Metabolic rate and tethered flight performance of male Bactrocera dorsalis (Hendel) (Diptera : tephritidae) fed nutritional and semiochemical supplements - Weldon, Christopher W. (University of Pretoria, 2024)
Dissertation (MSc (Entomology))--University of Pretoria, 2024.